Public Rental Housing and Long-Term Settlement Intention of the Migrants in China: The Mediating Effect of Identity - Cuicui Du; Wenlong Lou; Yuhua Qiao; Yongchao Zhang (Buildings, 2024)
The urban settlement of migrants and their families is an important aspect of new urbanization. Affordable housing, a key measure to improve their living conditions, can advance their urbanization goals. Based on the China Migrants Dynamic Survey (CMDS) data and land transaction data of cities, this study employs a complementary log–log model to estimate the effect of public rental housing (PRH) on the long-term settlement intention (LTSI) of migrants and delves into the intrinsic effect mechanism through the mediating effect. The results show that: (1) Living in PRH can significantly improve the LTSI of migrants who rent. A series of robustness tests and endogeneity tests support the validity of this conclusion; (2) The visualization of a heterogeneity analysis shows that PRH has a greater influence on the LTSI of first-generation migrants and urban–urban migrants. As the city class of the destination decreases, the effect of PRH gradually diminishes; (3) A mechanism analysis suggests that a sense of identity plays a mediating role in PRH affecting the LTSI of the migrants, particularly in first-tier cities. This paper enriches the literature related to the field of housing security programs, provides policy references for enhancing the LTSI of the migrants, and promotes the development of urbanization.